Microcystins production and antibacterial activity of cyanobacterial strains of Synechocystis, Synechococcus and Romeria isolated from water and coral reef organisms of Brazilian coast - Barboza, Giuseppe; Gorlach-Lira, Krystyna; Sassi, Cristiane; Sassi, Roberto (Revista de Biología Tropical, 2017)
Cyanobacteria are widely distributed in terrestrial, freshwater and marine environments, and over the past decades have been recognized as a powerful source of bioactive compounds. In this study, some cyanobacterial strains were isolated from samples of seawater, brackish water and tissue of reef benthic invertebrates (zoanthid Protopalythoa variabilis, the sponges Cynachrella sp. and Haliclona sp., the coral Siderastrea stellata, and ascidians), collected at the states of Paraíba and Rio Grande do Norte (Northeast of Brazil), during the period between July 2010 and February 2014. After standard isolation methods, the cultivation of the strains was carried out in acclimatized culture chamber (25 °C) under constant aeration, for 15 days at 12-hour photoperiod, using Conway and BG11 media made with filtered seawater. After ethanolic and methanolic extracts, the strains were analysed for the microcystin production by the ELISA technique and for the antibacterial activity against Staphylococcus aureus and Pseudomonas aeruginosa by the agar well diffusion method. The detection of the mcyB gene, one of the genes related to the microcystin synthesis, was done by the Polymerase Chain Reaction (PCR) technique. The majority of the eighteen cyanobacterial strains belonged to Synechococcaceae Family. The genera of Synechocystis, Synechococcus and Romeria were represented by ten, six and two strains, respectively. The production of microcystins was observed in five strains belonging to the genus Synechocystis. The presence of mcyB gene was detected in 12 strains of cyanobacteria: Synechocystis (three strains), Synechococcus (six strains) and Romeria (two strains). Only one strain (Synechocystis aquatilis) showed both the microcystin production and the mcyB gene presence. The antibacterial activity was observed for one strain of Romeria gracilis, one strain of Synechocystis aquatilis and two strains of Synechococcus sp. The ethanolic extracts of R. gracilis strain and two Synechococcus spp. strains inhibited the growth of P. aeruginosa. Among methanolic extracts of cyanobacteria, only one strain of S. aquatilis showed activity against S. aureus, and one R. gracilis strain against P. aeruginosa. Some cyanobacterial strains studied were positive for the microcystin production and antibacterial activity against pathogenic bacteria S. aureus and P. aeuruginosa, and may be further explored for additional biotechnological applications.